Como uma universidade corporativa desenvolve valores e competências organizacionais: estudo de caso da Universidade Corporativa Esho - Santos, José Antônio Alves dos (2009)
Ongoing changes in the world of business have led companies to conceive a wider perspective on Training and Development of their workers and cooperators, by emphasizing courses that allow their organization to keep their members updated on the constant and swift changes of the present world. This scenario gives rise to the concept of Corporate University, creating a significant differential in the personal and professional development of employees. The purpose of this study is investigating how a Corporate University develops in its workers and associates organizational values and competences to achieve the strategies proposed by companies. The methodology is based on quality research, whereby it develops a Case Study at Esho Network Corporate University. Twelve persons, amongst managers, professors and cooperators involved with this institution, were interviewed. The work was divided into four chapters. Chapter I is a preamble of the study, Chapter II presents its theoretical foundations, Chapter III defines its methodologies and Chapter IV describes the case study at ESHO Corporate University, analyzing the data of the research. Finally, Chapter V offers the conclusions and suggestions for future researches. The research data examined in light of the theoretical foundations evidences the model of Esho Network Corporate University fulfills its expectations - even though, in the opinion of the employees, it must work on some critical aspects -, and is key in developing the qualifications and competences required to sustain the company’s competitive advantage